Dual solutions of unsteady two-dimensional electro-magneto-hydrodynamics (EMHD) axisymmetric stagnation-point flow of a hybrid nanofluid past a radially stretching/shrinking Riga surface with radiation effect - Khashi’ie, Najiyah Safwa; Waini, Iskandar; Md Arifin, Norihan; Pop, Ioan (Emerald Group Publishing Ltd, 2023)
Purpose: This paper aims to analyse numerically the unsteady stagnation-point flow of Cu-Al2O3/H2O hybrid nanofluid towards a radially shrinking Riga surface with thermal radiation. Design/methodology/approach: The governing partial differential equations are transformed into a set of ordinary (similar) differential equations by applying appropriate transformations. The numerical computation of these equations including the stability analysis is conducted using the bvp4c solver. Findings: Two solutions are possible within the allocated interval: shrinking parameter, unsteadiness decelerating parameter, electro-magneto-hydrodynamics (EMHD) parameter, nanoparticles volumetric concentration, radiation parameter and width parameter, whereas the stability analysis certifies that the first (upper branch) solution, which fulfills the boundary conditions is the physical/real solution. The EMHD parameter generated from the application of Riga plate enhances the skin friction coefficient as well as the heat transfer process. The width parameter d is also one of the factors in the deterioration of the skin friction coefficient and heat transfer rate. It is crucial to control the width parameter of the magnets and electrodes to obtain the desired outcome. The radiation parameter is not affecting the boundary layer separation because the critical values are unchanged. However, the addition of radiation and unsteadiness decelerating parameters boosts the thermal rate. Originality/value: The results are novel and contribute to the discovery of the flow and thermal performance of the hybrid nanofluid subjected to a radially shrinking Riga plate. Besides, this work is beneficial to the other researchers and general audience from industries regarding the factors which contribute to the thermal enhancement of the working fluid.